Generalized difference strongly summable sequence spaces of fuzzy real numbers defined by ideal convergence and Orlicz function - Kilicman, Adem; Borgohain, Stuti (SpringerOpen, 2013)
We study some new generalized difference strongly summable sequence spaces of fuzzy real numbers using ideal convergence and an Orlicz function in connection with de la Vallèe Poussin mean. We give some relations related to these sequence spaces also.